Application of Knowledge Management in Efforts to Develop Human Resource at the Directorate General of Taxation : (Literature Review of Human Resource Management) - Faisal Roni Kurniawan; Widya Natalia Sirait; Shendy Arsela; Achmad Fauzi (Journal of Accounting and Finance Management, 2023)
Knowledge management presents an opportunity for changes in the field of information and libraries in order to create forms that are more relevant to changing times. The purpose of this research is to understand the application of knowledge management at the Directorate General of Taxation. The method used in this study is a simple qualitative method through field object observation techniques and literature review. Based on research results, the Directorate General of Taxation has implemented knowledge management very well and consistently so that efforts to achieve individual and organizational performance can be achieved significantly. Through the implemented knowledge management system, institutional transformation becomes faster because all kinds of knowledge can be properly archived and easily accessed by all employees.